Permanent Magnet Hall Thruster for satellite orbit raising with low power energy consumption - Ferreira, José Leonardo; Mourão, Decio Cardoso; Souza, João Henrique Campos; Carvalho, Guilherme Morais de; Possa, Gabriela Cunha; Moraes, Brunno Silva; Winter, Othon Cabo [UNESP]; Sandonato, Gilberto Marrega (My University, 2008)
Electric propulsion is now a succeful method for primary propulsion of deep space long duration missions and for geosyncronous satellite attitude control. Closed Drift Thruster, so called Hall Thruster or SPT (Stationary Plasma Thruster), was primarily conceived in USSR (the ancient Soviet Union) and, since then, it has been developed by space agencies, space research institutes and industries in several countries such as France, USA, Israel, Russian Federation and Brazil. In this work we present the main features of the Permanent Magnet Hall Thruster (PMHT) developed at the Plasma Laboratory of the University of Brasilia. The idea of using an array of permanent magnets, instead of an electromagnet, to produce a radial magnetic field inside the plasma channel of the thruster is very significant. It allows the development of a Hall Thruster with power consumption low enough to be used in small and medium size satellites. Description of a new vacuum chamber used to test the second prototype of the PMHT (PHALL II) will be given. PHALL II has an aluminum plasma chamber and is smaller with 15 cm diameter and will contain rare earth magnets. We will show plasma density and temperature space profiles inside and outside the thruster channel. Ion temperature measurements based on Doppler broadening of spectral lines and ion energy measurements are also shown. Based on the measured plasma parameters we constructed an aptitude figure of the PMHT. It contains the specific impulse, total thrust, propellant flow rate and power consumption necessary for orbit raising of satellites. Based on previous studies of geosyncronous satellite orbit positioning we perform numerical simulations of satellite orbit raising from an altitude of 700 km to 36000 km using a PMHT operating in the 100 mN - 500 mN thrust range. In order to perform these calculations integration techniques were used. The main simulation paraters were orbit raising time, fuel mass, total satellite mass, thrust and exaust velocity. We conclude comparing our results with results obtainned with known space missions performed with Hall Thrusters. © 2008 by the American Institute of Aeronautics and Astronautics, Inc.
Keywords: Aluminum plasmas; Deep space; Doppler broadening; Fuel mass; Integration techniques; Ion energy measurement; Ion temperature measurements; Long duration missions; Low Power; Medium size; Numerical simulation; Plasma channel; Plasma laboratories; Plasma parameter; Power Consumption; Primary propulsion; Propellant flow; Radial magnetic field; Rare earth magnet; Russian federation; Satellite attitude control; Satellite mass; Satellite orbit; Soviet Union; Space agency; Space missions; Space research institute; Specific impulse; Spectral line; Stationary plasma thruster; Vacuum chambers; Electric propulsion; Energy utilization; Magnetic devices; Magnetic fields; Navigation; Orbits; Permanent magnets; Plasma density; Plasma devices; Plasmas; Satellites; Space research; Spectroscopy; Temperature measurement; Hall thrusters